Videofluoroscopic swallowing study predicts clinical outcomes in critically Ill children with dysphagia: a retrospective observational study - Yoonju Na; Jaeyoung Choi; Jihong Choi; Su Mi Oh; Hyuna Jang; Suein Choi; Joongbum Cho; Jeong-Yi Kwon (Frontiers in Pediatrics)
BackgroundThis retrospective observational study aimed to investigate the features of acute dysphagia observed during videofluoroscopic swallowing study (VFSS) in critically ill children and their potential to anticipate clinical outcomes.MethodsAdministrative healthcare data of children aged 1–18 were analyzed. Data were collected from the pediatric intensive care unit (PICU) of a single tertiary medical center in South Korea between March 2019 and December 2022. We reviewed VFSS conducted on patients in the PICU who were referred by clinicians suspecting dysphagia.ResultsA total of 36 children were included in the study; 52.8% exhibited aspiration on VFSS. In this investigation, participants were provided with pureed food, liquids, solids, and a combination of solids and liquids (referred to as mixed) during the examination. Any occurrence of aspiration throughout the examination was deemed as aspiration. All individuals displaying aspiration were found to have silent aspiration. Silent aspiration was associated with a longer length of stay (LOS) in the PICU. Logistic regression analysis revealed that the time from PICU admission to VFSS and intubation duration significantly influenced LOS. Abnormal findings in the VFSS, including aspiration, delayed swallowing reflex, insufficient laryngeal closure, and residue, were statistically significant variables in determining the feeding mode at discharge.ConclusionThis study highlights the importance of VFSS in assessing swallowing function in critically ill children. It suggests that VFSS findings, such as silent aspiration, can aid in predicting patient outcomes, including LOS and the delay in oral feeding.